Improvement of persistent impairments in executive functions and attention following electroconvulsive therapy in a case control longitudinal follow up study - Åsa Hammar; Eivind Haga Ronold; Malene Alden Spurkeland; Rita Ueland; Ute Kessler; Ketil J. Oedegaard; Leif Oltedal (BMC Psychiatry)
Abstract Background How cognition is influenced by electroconvulsive treatment (ECT) and major depressive disorder (MDD) is still debated. The development and etiology of neurocognitive impairment in MDD were examined by investigating the cognitive profile following ECT related to the state, scar, and trait perspectives, with the former predicting improvements parallel with depressive symptoms, while the two latter expected persisting impairments. Executive functions (EF) and attention are central to cognition and alterations in these functions could influence other domains like memory. The main aims of the present study were to examine the short and long-term effects of ECT on EF and attention in patients with major depressive disorder by exploiting the rapid antidepressant effect of this treatment. Methods A case-control longitudinal follow-up design was used to investigate the effects of unilateral brief-pulse ECT on EF and attention in patients with depression (n = 36) compared to untreated healthy controls (n = 16). EF and attention were measured pre-treatment, approximately two weeks, and six months post-treatment. Results The patient group showed significantly worse performance on most tests compared to healthy controls pre-treatment, and no short- or long-term worsening of EF and attention following ECT was found. Significant improvement was identified in patients’ attention, processing speed and inhibition after ECT. Conclusions The present study showed that there was no cognitive worsening after ECT treatment. An improvement in several of the tests measuring inhibition, attention, and processing speed was parallel to symptom reduction, with the former showing associations to symptom change, suggesting state-related effects from improved mood. Still, the patient group performed significantly worse on most measures both pre-treatment and at the short and long-term follow-ups, indicating prevailing trait or scar effects on cognitive functions and potential lack of practice effects. Clinical trial number NCT04348825 (14.04.20).